Effect of brand image of Bata branded products on customer loyalty in ringroad city walk Medan - Elly Ria, Chainar (JURNAL GLOBAL MANAJEMEN; Vol 10 No 1 (2021): JUNIDO - 10.46930/global.v10i1.1107, 2021)
Abstract : The formulation of the problem in this study is whether the brand image has influenced consumer loyalty of Bata brand products at the Medan City Walk Ringroad Bata outlets. The purpose of this study was to determine the effect of Bata brand image on consumer loyalty at outlets Bata Ringroad City Walk Medan. This research was conducted in the scope of the Bata brand Ringroad City Walk Medan outlets, with the object of research being limited only to the brand image variable as the independent variable and consumer loyalty as the dependent variable. The population in this study were 240 people and then a sample of 23 people was taken. This research was conducted using SPSS version 21.0 software and also using a simple linear regression test that got the result Y = 6.016 + 0.803X. From this equation it can be interpreted that the variable brand image has a significant effect on consumer loyalty of the Bata brand product at the Bata Ringroad City Walk Medan outlet. For the influence of the variable brand image on consumer loyalty is 0.000 <0.05 and thit 11.977> ttab 1.721, meaning that there is an effect of brand image on consumer loyalty. And based on the coefficient of determination, it can be explained from the results, which is 86.6% and the remaining 13.4% is explained by other variables. It is recommended that the Bata Ringroad City Walk Medan to maintain its existing brand image. By improving product quality and prioritizing excellent service